As políticas de inovação das instituições científicas, tecnológicas e de inovação (ICT) no contexto das encomendas tecnológicas - Nathália Domingues Oliveira Barbosa (2021)
This work aimed at providing elements to understand the influence of the Innovation Policies of Scientific, Technological and Innovation Institutions (ICT) and their respective ecosystems of entrepreneurship and innovation in the consolidation of contracts between these institutions and the State for innovation procurement. Hired innovation development through technological order contracts is characterized by technological risk and is an important mean for the State to achieve the development of technological solutions. Through them, the society may acquire new products, goods, and services, contributing to the diffusion of technology and the creation of new markets, in addition to enabling to solve social problems through technology. For the full operationalization of this procedure in the Brazilian National Innovation System (SNI), characterized by the concentration of scientific and technological activities in ICT with little innovative contribution of companies, the interaction between ICT and companies combining skills for ETEC may be essential, as discussed in this research. To achieve the aim of this work, interviews were conducted with two Brazilian references in terms of ETEC, and two cases were selected for the study. A survey was also carried out on the treatment given to ETEC in the Innovation Policies of ICT in Brazil, based on data from thirty-six Brazilian ICT. After collecting the data and analyzing the results, enough elements were not found to prove the direct relationship between the Innovation Policies of the ICT and the hiring of the institutions studied for the technological orders contracts. The results obtained provide evidence of the influence of the infrastructure of research and technological development for hiring ICT in ETEC. Regarding the interaction between ICT and companies, the findings of this research indicate that the set of skills between these agents is essential to potentiate ETEC in the context of the Brazilian SNI. From the results and the discussion of the propositions that guided this research, it was possible to outline a set of guidelines to contribute to the norms and practices of ICT in terms of ETEC and catalyze the hiring and performance of these institutions in ETEC. These guidelines comprise the following axes: normative; entrepreneurship and innovation ecosystem; management and professional skills.